Аноплоцефалидозы (anoplocephalo- doses) лошадей в Узбекистане (FAN va JAMIYAT, 2017)
The article deals with the horses’ deсease caused by helminthes of three kinds that are called Anaplocephalidos of horses. Donkeys and mules are susceptible to the family of Anoplocephalidae helminths. Three kinds of the family Anoplocephalidae are (Anoplo- cephala magna), (Anoplocephala perfoliata) and rarely - (Paranoplocephala magna). The mucous membrane of a lean gut bluetongue is inflamed, bulked up, with centre reddening and it is plentifully covered by slime of horses.